Characterization of the Bioactivity and Mechanism of Bactenecin Derivatives Against Food-Pathogens - Sun, Changbao; Gu, Liya; Hussain, Muhammad Altaf; Chen, Lijun; Lin, Li; Wang, Haimei; Pang, Shiyue; Jiang, Chenggang; Jiang, Zhanmei; Hou, Juncai (Frontiers in Microbiology, 2019)
With the emergence of multidrug-resistant bacteria, antimicrobial peptides (AMPs) are regarded as potential alternatives to traditional antibiotics or chemicals. We designed and synthesized six derivatives of bactenecin (L2C3V10C11, RLCRIVVIRVCR), including R2F3W10L11 (RRFRIVVIRWLR), R2W3W10R11 (RRWRIVVIRWRR), K2W3V10R11 (RKWRIVVIRVRR), W2R3V10R11 (RWRRIVVIRVRR), W2K3K10R11 (RWKRIVVIRKRR), and K2R3R10K11 (RKRRIVVIRRKR), by amino acid substitution to increase the net charge and reduce hydrophobicity gradually. The bioactivity and mechanisms of action of the designed peptides were investigated. The results indicated that the antimicrobial activity of the designed peptides was higher than that of bactenecin. The hemolytic activity and cytotoxicity of the designed peptides were significantly lower than those of bactenecin. The designed peptides exhibited a wide range of antimicrobial activity against food-pathogens, particularly peptides K2W3V10R11 and W2R3V10R11; in addition, the activity was maintained under physiological salt and heat conditions. Mechanism studies indicated that AMPs interacted with negatively charged bacterial cell membranes, resulting in the destruction of cell membrane integrity by increasing membrane permeability and changing transmembrane potential, leading to cell death. The present study suggested that peptides K2W3V10R11 and W2R3V10R11 exhibited potential as alternatives to traditional antibiotics or chemicals for the treatment of food-pathogens. These findings lead to the development of a potential method for the design of novel AMPs.